STUDY OF STABILITY AND EXPIRATION DATE ESTABLISHIMENT OF MICROPARTICLES OF ALPRAZOLAM ON THE BASIS OF POLY-D,L-LACTIDE-CO-GLYCOLIDE - A. I. Medvetskiy; L. I. Scherbakova; V. A. Kompantsev; L. P. Gokghayeva; T. M. Vasina (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2015)
Stability of microparticles of alprazolam in natural conditions was studied by the method of "accelerated aging". It was established that microparticles of alprazolam were not exposed to disruption and their appearance was not altered during the research. Expiration dates of alprazolam microparticles determination was calculated using the formula of J.H. van't Hoff. The expiration date made 2 years.